New directions for technical cooperation among developing countries (UNDP New YorkUS, 1996)
Examines the experience in technical cooperation among developing countries (TCDC) since the adoption in 1978 of the buenos Aires Plan of Action for Promoting and Implementing Technical Cooperation among Developing Countries in an effort to identify salient features of that experience and the lessons learnt from it.
DC